Marketing Communication of South Kalimantan Shari'ah Bank branch of Kayutangi In Attracting Customers' Interests - putri ayu hidayatur rafiqoh (Islamic Economics and Business Faculty of UIN Antasari, 2020)
Marketing communication is a marketing activity that aims to inform about a product or service offered by a persuasive company to prospective buyers or consumers. Banking competition that is enlivened by conventional banks and Islamic banks makes consumers have many choices to invest. Marketing communication is needed because with marketing communication, it is expected that there are three changes (knowledge, attitude, and desired action). The South Kalimantan Shari'ah Bank Kayutangi conducts sales promotions by conducting field outreach to various agencies , Personal selling by visiting prospective customers directly to their place, Public relations by participating in various events, and Advertising by distributing brochures & calendars. And then, class/training related to communication skills need to be followed by marketers to improve their ability to carry out marketing activities. And the last, supporting facilities also needed in order to optimize the performance of marketing communications.